Creating resilient water governance for irrigated producers in Mendoza, Argentina. Issue 58 (April 2016) - Hurlbert, Margot; Mussetta, Paula
Highlights: Water governance instruments and producer capitals impact adaptation. Centuries old water practices are best augmented with new practices. Considering drivers, instruments, and capitals allows consideration of inter-linkeage. Abstract: This research explores the institutional water governance system of irrigated agricultural producers in Mendoza, Argentina in the context of a changing climate (predominantly increasing events of drought and water scarcity). An assessment is made of the impact of water governance instruments on producers using the methodology of vulnerability and adaptive capacity. Analysis focuses on the impact of the institutional water governance system on the adaptive capacity of producers' resources, or capitals (human, social, economic, technological, and natural). Conclusions and suggestions for improving the resiliency of agricultural producers and increasing the adaptive dimensions of Mendoza's water governance system are made based on this analysis.